PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HORAY (CRH) TERHADAP HASIL BELAJAR FISIKA PADA MATERI SUHU DAN KALOR KELAS X MAN KISARAN T.P 2013/2014 - Lely Safitri Ritonga; Ratna Tanjung (UNIVERSITAS NEGERI MEDAN, 2014)
ABSTRACT This study aims to determine the effect of Type Cooperative Learning Model Course Review horay (CRH) Against the Physics Learning Outcomes In Topic Temperature and Heat In Class X Semester II MAN Kisaran T.P 2013/2014. Type of study is a quasi experiment with two group pretest posttest design. The population in this study were all students of class X MAN Kisaran T.P 2013/2014 which consists of 7 classes of 245 students. Samples were taken by means of random cluster sampling, consists of two classes, namely classes XA and XB as a class experiment as a control class consisting of 35 students. Instruments used are two, 1) test learning outcomes and 2) Observation Sheet. Achievement test of 20 multiple-choice questions with 5 options and have divalidkan by 3 validator. Observation sheet consists of assessment activity, affective and skills. Hypothesis testing using t-test. From the analysis of the data obtained experimental class average pretest score=31.3 with a standard deviation=7.4 and the average post-test score= 6.4 with a standard deviation=9.0. While in the control class average pretest score=29.7 with a standard deviation=7.2 and the average post-test score=64.7 with a standard deviation=8.9. Average learning activities in the classroom experiment=85.70% and the grade control=76.52%, so the average activity concluded the experimental class students is higher than the control class. Average grade student affective experimental = 60.00% and grade control=54.6%, so the average inferred affective experiment class higher than the control class. Average grade students skills experiment, at a meeting of the I=58.2%, II=62.35% meetings, meetings and III 62.7%=71.1% IV meeting. So the average value during the learning skills of students=63.7% with active criteria. Data obtained from testing the hypothesis that the post-test t =5.45 at significance level α=0.05 and price table=1.99. So tcount>t table (5.45>1.99), then Ha is accepted. It can be concluded that there is a difference due to the effect of the application of cooperative learning model physics CRH on learning outcomes of students in the subject matter of temperature and heat of class X Semester II MAN Kisaran. Keywords: cooperative type CRH, quasi experiment, learning results